2005
DOI: 10.1373/clinchem.2004.040063
|View full text |Cite
|
Sign up to set email alerts
|

Negative Interference in Cardiac Troponin I Immunoassays by Circulating Troponin Autoantibodies

Abstract: Background: There are numerous potential sources of interference in immunoassays. Our aim was to identify the blood component that causes negative interference in cardiac troponin I (cTnI) immunoassays based on antibodies against the central part of cTnI. Methods: We isolated an interfering factor (IF) from a sample with low recovery of added cTnI, using several consecutive purification steps: caprylic acid precipitation, ammonium sulfate precipitation, and purification on Cibacron Blue gel and protein G colum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(68 citation statements)
references
References 41 publications
1
65
0
2
Order By: Relevance
“…Although the incidence of assay interferences caused by atypical antibodies has been reduced, all immunoassays have the potential for both false-positive and false-negative interference (23,24 ).…”
Section: Overview Of Other Etiologies a Background And Scopementioning
confidence: 99%
“…Although the incidence of assay interferences caused by atypical antibodies has been reduced, all immunoassays have the potential for both false-positive and false-negative interference (23,24 ).…”
Section: Overview Of Other Etiologies a Background And Scopementioning
confidence: 99%
“…Historically, autoantibodies to cTnI have caused negative interference in some cTnI immunoassays [24,25]. Investigation of the epitope specificity of cTnI autoantibodies has shown that the cTnI midfragment (amino acids 30-100) is the commonest target of these antibodies [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work from our laboratory and others has focused on the dysregulation of the immune system as an essential modulator of disease induction and progression in heart failure (1,2). In this context, release of cardiac troponin I (TnI) from damaged cardiomyocytes into the circulation is believed to trigger an autoimmune response to TnI (3,4).…”
mentioning
confidence: 99%